Kandungan krom tanaman kacang tanah yang dipupukdengan kompos yang mengandung kromosal - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
The study was done to know the effect of chromosal and sludge of tanning wastewater on the chrome content of peanut forage manured by compost. The study was conducted in laboratory scale by mean of planting the peanut in plastic polybag that was filled with 1 kg of land and 300 g of compost. The peanut was planted in the medium and manured by chromosal solution or sludge of tanning wastewater. The study was devided into two experiments, first was to study the effect of chromosal solution on plant production and chrome content, second was to study the effect of sludge of tanning wastewater on plant production and chrome content of the plant. The first experiment consisted of five treatments i.e P0, P1, P2, P3 and P4, respectively, Oppm, 100ppm, 200ppm, 300ppm and 400 ppm of chromosal supplementation. The second experiment consisted of five treatments i.e KO, Kl, K2, K3 dan K4, respectively, 0%, 1%, 2%, 3% and 4% of sludge suplementation. Each polibag was planted with two peanut seeds, and then plaCed in a green house. After the plant came out, it was watered with 20 ml of chromosal solution in the first experiment and 20 ml of water in the second experiment, every two days. All peanut plantation were harvested at 35 days old, followed by weighing the plant production and analysing chemically for water content, ash content and chrome content. This experiment used completely randomised design (CRD) and the collected data were analysed statistically by analysis of variance. Differences between the treatment means were tested by Duncant Multiple Range Test. The results indicated that more chromosal levels added into the plantation medium resulted more chrome absorbed by peanut plant. The chromosal addition did not have any negative effect on the forage production , but the sludge addition had negative effect on plant growth and forage production due to the phytotoxin. The chrome content of the peanut plant added by 0%, 1%, 2%, 3% and 4% was 4.250 ppm, 4.115 ppm, 4.782 ppm, 4.364 ppm and 4.931 ppm, respectiyely. The peanut plantation added by chromosal solution for 0 ppm, 100 ppm, 200 ppm, 300 ppm and 400 ppm had higher absorbtion ability amounting to 5.275 ppm, 6.394 ppm, 11.482 ppm, 25.573 ppm and 10.447 ppm. it was concluded that the chrome metal could be absorbed by peanut plant. Increasing chromosal level did not reduce forage production, but increased chrom content of the peanut plant. Increasing sludge level reduced the forage production, but did not increase chrome content of peanut plant.